The Relationship between Physical Activity Levels and Psychological Resilience of University Students - Seçer, Emrah (2020)
The aim of this study is to investigate the relationship between physical activity levels and psychological resilience of university students. The survey model, which is one of the quantitative research types, has been used in the research. The research group consists of 1734 students - 725 (41.8%) males and 1009 (58.2%) females) - studying at Erzincan Binali Yıldırım University. Psychological Resilience Scale (PRS) and International Physical Activity Questionnaire (IPAQ) data was used as a collection tool. Descriptive statistics, chi-square test of independence, independent samples t-test, Anova (Tukey), correlation, and regression tests have been used in the analysis of the data. As a result of the study, it has been seen that physical activity levels of men were higher than women and that there was no significant difference between the groups' psychological resilience. And when body mass indexes were examined, it was observed that physical activity levels of those with thin index were higher than those with normal and overweight index. In addition, a significant low-level positive correlation has been found between the physical activity levels. Physical activity level is a variable that predicts psychological resilience level.